Altapress on assessing the effectiveness of a community health campaign on hypertension in improving the healthseeking behavior of residents in a lower middle-income barangay - Aguinaldo, Hannah Franada 1997-; Uezono, Deniel Robles (2018)
"According to the Global Burden of Disease, non-communicable diseases would account for seven out of 10 death by 2020. In the Philippines, cardiovascular diseases are come of the leading causes of mortality. However, despite the alarming number of cases of hypertension and heart-related diseases, there are still no established campaigns on hypertension. Previous studies have shown that culturally appropriate campaigns and promotions are most effective in preventing and managing these types of diseases. This study developed and implemented a community health campaign related to hypertension, which made use of communication materials consisting of a booklet, calendar, and text brigades. Its effectiveness was tested using a quasi-experimental design. Results showed that there was a greater improvement of health-seeking behavior in the experimental group. In a situation where there were little to no efforts from the barangay health center and health institutions to promote hypertension management in a community level, the improvement can be strongly attributed to the community health campaign."